2019
DOI: 10.1515/jbcpp-2019-0250
|View full text |Cite
|
Sign up to set email alerts
|

Medical problems in patients with chronic kidney disease undergoing hemodialysis and their therapy

Abstract: Background It was reported that hemodialysis (HD) with either a new or reused dialyzer raises medical problems that require therapeutic regimens. This study aimed to investigate the medical problems and their management in patients undergoing HD. Methods This study was conducted by prospectively observing patients with chronic kidney disease undergoing HD. The incidence of medical problems and the treatment given were recorded. Results Among 351 cases of HD, medical problems occurred in 15.7% of cases, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The discomfort produced by these intradialytic symptoms could be the cause of early cessation of HD session in up to 30% of patients. 32 , 33 In the present study, the number of patients and episodes of muscle cramps during HD were remarkably lower among those who received the high dialysis magnesium concentration. In a small observational study, increasing the dialysis magnesium concentration from 0.5 to 1 mEq/L resulted in a lower frequency of and less severe muscle cramps.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…The discomfort produced by these intradialytic symptoms could be the cause of early cessation of HD session in up to 30% of patients. 32 , 33 In the present study, the number of patients and episodes of muscle cramps during HD were remarkably lower among those who received the high dialysis magnesium concentration. In a small observational study, increasing the dialysis magnesium concentration from 0.5 to 1 mEq/L resulted in a lower frequency of and less severe muscle cramps.…”
Section: Discussionsupporting
confidence: 44%
“…Muscle cramping is the second most common intradialytic symptom after hypotension. The discomfort produced by these intradialytic symptoms could be the cause of early cessation of HD session in up to 30% of the patients 32,33 . In the present study, the number of patients and episodes of muscle cramps during HD were remarkably lower among those who received high dialysis magnesium.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The severity of pruritus is examined in patients using VAS 22 . Intravenous dexamethasone and diphenhydramine are used to treat this condition 23 …”
Section: Discussionmentioning
confidence: 99%
“…22 Intravenous dexamethasone and diphenhydramine are used to treat this condition. 23 A study examining the relationship between xerosis and pruritus found that itching increased dramatically with the severity of dry skin. 24 Another common skin manifestation in patients undergoing hemodialysis is subungual hyperkeratosis.…”
Section: Discussionmentioning
confidence: 99%